Taman Pendidikan Bahasa Inggris (TPBI): Kursus Bahasa Inggris Gratis bagi Murid Madrasah Diniyah Takmiliyah (MDT) - Purwaningsih, Sundari; Hakim, Lystiana Nurhayat; Solihati, Tri Agustini; Julistiana, Risma (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2025)
The English Learning Oasis or Taman Pendidikan Bahasa Inggris (TPBI) program was a community service committed to providing free English courses to students of Madrasah Diniyah Takmiliyah (MDT) or an islamic enrichment school. This community service was given to the 4th-grade students of MDT Al Mujahidin, one of MDTs in Cikunir, Singaparna, Tasikmalaya Regency. Most of the students do not receive English lessons at their school. The program aimed to improve these MDT students’ interest and skills in English. In this English course, they learned four language skills; listening, reading, speaking, and writing. The teaching team for this course consisted of students majoring in English Education Department of Universitas Perjuangan Tasikmalaya. This community service was executed in seven stages; needs analysis, pretest, syllabus design, lesson planning, dissemination of the lesson plan, implementation of the English course, and evaluation (posttest and perception survey). This English course yielded positive results in two areas. First, this English course was proven to increase students English learning outcomes. It can be seen from the average score of posttest (88) which was higher than that of pretest (53,59). Second, the students developed positive attitudes and interest in English. The initial survey indicated that 16% of the students did not desire an English course while the final survey revealed that 100% of the students wish for the continued implementation of the English course.